Development of a Multidimensional Pain Questionnaire in Professional Dance (MPQDA): a pilot study - Jasmin Haenel; Thomas Schoettker-Koeniger; Eileen M. Wanke (BMC, 2022)
Abstract Background Pain is part of the everyday life of professional dancers. It can indicate health risks and impair the ability to work. Suitable screening tools can be used to identify pain and its risk potential. A comprehensive, multidimensional, differentiated assessment tool for pain in professional dance does not currently exist. Methods An initial questionnaire was developed in German and English and was assessed in a qualitative pretest. In a field study with a cross-sectional design including n = 72 dancers from Germany (n = 36 responses each in the English and German language versions), the questionnaire was optimized by item analysis, its psychometric properties (dimensionality, construct validity, reliability) were examined and the ability of the pain dimensions to classify the subjective ability to work in training was analyzed (ROC analysis). Results The developed Multidimensional Pain Questionnaire in Professional Dance (MPQDA) was reduced and optimized in its psychometric properties. Following questions were reduced in their items or answer categories: pain localizations (from 20 to 15 regions), accompanying symptoms (from 6 to 3 items), sensory and affective pain quality (from 20 to 10 items), pain frequency (from 4 to 3 answer categories), and the motives of working with pain (from 14 to 12 items). Regarding the subjective ability to work in training, the variables of the ability to work in rehearsals and in performances, as well as the accompanying symptoms of tension and mobility restrictions, showed a relatively good classification ability (Area under the Curve (AUC) ≥ 0.7 in the 95% confidence interval) and significant, moderate to strong correlations (Somers' D > 0.25, p < 0.05). The classification ability of the other pain dimensions was largely absent or poor. Conclusion The MPQDA differentiates various pain dimensions in professional dancers and is available in a compatible manner in German and English. The clinical relevance needs to be explored further in the future.